Pembelajaran Matematika bagi Siswa Madrasah Ibtidaiyah Berbasis Edugame Wordwall - Maftuhah, S. (Madrasah Ibtidaiyah Education Journal, 2023)
This research aims to discuss how the game wordwall is used as a mathematics learning media at Madrasah Ibtidaiyah. This research uses qualitative methods with data sources from interviews and observations. The data obtained was then analyzed to obtain a general picture of the use of the game word wall learning media in fifth-class mathematics learning at MI Islamiyah Banin. The research results showed that there were changes in attitudes that occurred in students after learning using the game Wordwall media. These changes can be seen from the aspect of student activity and the observation assessment criteria are measured through several indicators, including student activity when participating in teaching and learning activities, student activity when submitting assignments on time, and asking questions about material that is not yet understood.